Моніторинг стану сформованості культури здоров’я майбутніх учителів фізичної культури: критерії та результативні показники - Мосейчук, Юрій (Український Педагогічний Журнал Інститут педагогіки НАПН України, 2019)
У статті проаналізовано сутність моніторингу, що виступає засобом для комплексної діагностики професійної підготовки студентів як майбутніх фахівців з фізичної культури. З’ясовано, що грамотно організований моніторинг забезпечить дослідження стану сформованості культури здоров’я у майбутніх учителів фізичної культури та дасть змогу спрогнозувати спектр конкретних показників. Встановлено, що якість одержаної інформації шляхом моніторингу повинна бути об’єктивною, надійною, повною, точною, адекватною, доступною й своєчасною. З практичної точки зору увагу моніторингу зосереджено на стані сформованості конкретних показників мотиваційного-ціннісного компоненту культури здоров’я. Саме показники роблять доступними облік й фіксування отриманих результатів. Акцент зроблено на характеристиці стану сформованості таких показників, як вміння позитивно мотивувати себе та сформованість ціннісних орієнтацій. Для визначення стану сформованості цих показників для моніторингового дослідження розроблено та під час дослідження апробовано конкретний діагностичний інструментарій. Проведений моніторинг довів, що майбутні учителі фізичної культури не заперечують вагомості культури здоров’я, з’ясовано, що формування мотиваційної сфери відбувається стихійно та потребує вдосконалення.
MONITORING THE SITUATION OF HEALTH CULTURE OF FUTURE TEACHERS OF PHYSICAL CULTURE: CRITERIA AND PERFORMANCE INDICATORS
The article analyzes the essence of monitoring, which serves as a tool for comprehensive diagnostics of students’ professional training as future specialists in physical culture. It has been found out that competently organized monitoring will provide the study of the state of the formation of the health culture of future teachers of physical culture and will enable to predict the range of specific indicators. It has been established that the quality of information received through monitoring should be objective, reliable, complete, accurate, adequate, accessible and timely. From a practical point of view, monitoring is focused on the state of formation of specific indicators of the motivational-value component of the health culture. It is the indicators that make accounting and recording of the results available. The main focus is on the characterization of the state of formation of indicators such as the ability to positively motivate themselves and the formation of value orientations. To determine the state of formation of these indicators, during the monitoring study, a specific diagnostic toolkit was developed. Summarizing the presented information, we believe that monitoring can be a real tool for collecting and processing information about the state of health culture of future teachers of physical culture. The results of the study indicate that students have a general idea of the importance of a health culture for fulfilling their professional tasks, and are aware of the need for improvement. It was found that interviewed respondents understand that their future professional activities are related to the need to have a high level of health culture, but they are not able to form it. Consequently, the carried out monitoring proved that future teachers of physical culture do not deny the importance of a health culture, but it was found that the formation of a motivational sphere is spontaneous and needs to be improved.
Keywords: моніторинг; критерії моніторингу; показники; культура здоров’я; майбутні учителі фізичної культури